THE IMPORTANCE OF LINGUOPOETIC ANALYSIS IN EDUCATION - Shomirzayeva Sevinch Usmon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Article  explores  the  significance  of  linguopoetic  analysis  in  education, emphasizing  its  role  in  enhancing  language  comprehension,  creativity,  and  critical thinking among students. Linguopoetics, which examines the aesthetic and expressive dimensions  of  language,  offers  valuable  insights  into  how  language  functions  in various contexts, particularly in literature and everyday communication. By integrating linguopoetic  principles  into  educational  practices,  educators  can  foster  a  deeper appreciation  for  language,  encourage  creative  expression,  and  develop  students' analytical skills. The article discusses practical applications of linguopoetic analysis in the  classroom,  including  the  analysis  of  literary  texts,  poetry,  and  other  forms  of discourse.  It  also  highlights  the  benefits  of  promoting  linguistic  awareness  and sensitivity  to  the  nuances  of  language,  ultimately  contributing  to  more  effective communication and a richer educational experience.